Sustainability, Social Responsibility, and Innovations in Tourism and Hospitality / Edited by H.G. Parsa ; Vijaya "Vi" Narapareddy, consulting editor ; SooCheong (Shawn) Jang associate editor - Jang, SooCheong (Shawn)Associate editor
Includes bibliographical references and index.